Characterization of copper sulfide nanostructured spheres and nanotubes synthesized by microwave-assisted solvothermal method - Thongtem T. (2014)
Copper sulfide nanostructured spheres and nanotubes were successfully synthesized, using a microwave-assisted solvothermal method, by the decomposition of [Cu(CH3CSNH2)2]Cl2 complexes, formed by the reaction of CuCl2·2H2O and CH3CSNH2 in ethylene glycol at different pH values, and identified by CHNS/O and FTIR analyses. The decrease in bonding energy of N-H revealed the coordination of copper ions and thioacetamide molecules. It was specified that nitrogen atoms of thioacetamide molecules were used to form Cu-thioacetamide complexes. XRD, SEM, TEM and SAED analyses show that the products were hexagonal CuS spheres in an extremely low pH solution, and hexagonal CuS nanotubes at a pH 13. Their Raman spectra show sharp peaks at 473 cm- 1, identified as the S-S stretching mode of S2 ions at the 4e sites. © 2009 Elsevier B.V. All rights reserved.